Definitions for the Sonographic Features of Joints in Healthy Children. Issue 1 (January 2015) - Roth, Johannes; Jousse-Joulin, Sandrine; Magni-Manzoni, Silvia; Rodriguez, Ana; Tzaribachev, Nikolay; Iagnocco, Annamaria; Naredo, Esperanza; D'Agostino, Maria Antonietta; Collado, Paz; the Outcome Measures in Rheumatology Ultrasound Group
<x xml:space="preserve">Abstract</x> Objective Musculoskeletal ultrasonography (US) has potential in the assessment of disease activity and structural damage in childhood arthritides. In order to assess pathology, the US characteristics of joints in healthy children need to be defined first. The aim of this study was to develop definitions for the various components of the normal pediatric joint. Methods The definitions were developed by an expert group and applicability was assessed on a collection of standardized scans of the knee and ankle joints by scoring the scans on a Likert scale. The definitions were then modified and applicability was reassessed before sending the definitions for approval to a larger panel of experts. A final scoring on stored images of all relevant joints at different ages followed. Results Five definitions were developed addressing the articular bone, cartilage, joint capsule, epiphyseal ossification center, and synovial membrane. In total, 224 US images of knees and ankles were acquired, of which 172 were selected for scoring. An agreement of ≥80% was not met for any of the definitions, but after modifications, 81–97% agreement was reached. This version of the definitions was approved by 15 US experts. In the final validation exercise, all definitions reached an agreement of ≥80% for the shoulder, elbow, wrist, metacarpophalangeal hip, knee, ankle and metatarsophalangeal joint. Conclusion US definitions for the normal pediatric joint were successfully developed through a Delphi process and validated in a practical exercise. These results provide the basis to develop definitions for pathology and to support the standardized use of US in pediatric rheumatology.